2016
DOI: 10.5535/arm.2016.40.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Compression Caused by Popliteus Muscle Enlargement Without Discrete Trauma

Abstract: Popliteal entrapment syndrome caused by isolated popliteus muscle enlargement is very rare, although its occurrence has been reported after discrete trauma. However, popliteal artery stenosis with combined peroneal and proximal tibial neuropathy caused by popliteus muscle enlargement without preceding trauma has not been reported. A 57-year-old man presented with a tingling sensation and pain in his left calf. He had no previous history of an injury. The symptoms were similar to those of lumbosacral radiculopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…2,4,11,12,[14][15][16][17][18] The femoral nerve (FN) descends in a groove between psoas and iliacus muscles, deep to the iliac fascia, passing under the inguinal ligament and it enters the thigh where it gives its terminal branches. 5,19,20 Compression to the FN has mostly been described as being due to bleeding disorders, when an iliac haematoma compresses it at three possible levels: against the inguinal ligament; at its lumbar roots; or in the space between the psoas and iliacus muscles where the overlying fascia is thicker. [20][21][22][23][24] The principal symptoms are thigh weakness along with the anterior thigh and medial leg numbness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,11,12,[14][15][16][17][18] The femoral nerve (FN) descends in a groove between psoas and iliacus muscles, deep to the iliac fascia, passing under the inguinal ligament and it enters the thigh where it gives its terminal branches. 5,19,20 Compression to the FN has mostly been described as being due to bleeding disorders, when an iliac haematoma compresses it at three possible levels: against the inguinal ligament; at its lumbar roots; or in the space between the psoas and iliacus muscles where the overlying fascia is thicker. [20][21][22][23][24] The principal symptoms are thigh weakness along with the anterior thigh and medial leg numbness.…”
Section: Introductionmentioning
confidence: 99%
“…When severe, the patient may be unable to stand without support. [19][20][21][22][23][24][25] Several reports have described variant muscular slips or sheets forming longitudinal fascicles or wide bands associated with psoas and iliacus, but most of them are not related to the FN. 1,4 The iliopsoas tendon or muscle may be split by the FN, but we have found only two reports that describe the FN itself being split by iliopsoas muscle slips.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that PM syndrome was caused by an isolated PM due to compression of the neurovascular bundle. In this case, the patient felt calf pain and numbness in the posterolateral aspect of the calf and sole [ 17 ]. Because the PM and popliteal artery are adjacent to each other, the condition of this muscle affects the blood circulation of the popliteal artery.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we surveyed the results of previous studies examining the shape of the PM and the surrounding structures to which it is connected [ 1 , 16 , 17 ]. The PM was shown to have a triangular shape [ 2 ] and is attached to surrounding ligaments and meniscus [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main etiological reason for PTN entrapments is space-occupying lesions. We found several cases in the literature: tibial arterial aneurysm [18] and pseudoaneurysm [16], intraneural ganglion cysts [19], Baker's cysts [20], tibial bone exostosis [21], and popliteal muscle enlargement [22]. In these cases, the space-occupying lesions either shifted the nerve to the fibrous sling of the soleus muscle or were the primary reason for entrapment, by compressing the nerve with mass effect.…”
Section: Anatomy Etiology and Pathophysiologymentioning
confidence: 99%